Growth Kinetics and Distribution of Trace Elements in Precious Corals - Vielzeuf, Daniel; Gagnon, Alexander C.; Ricolleau, Angèle; Devidal, Jean-Luc; Balme-Heuze, Catherine; Yahiaoui, Nassima; Fonquernie, Claire; Perrin, Jonathan; Garrabou, Joaquim; Montel, Jean-Marc; Floquet, Nicole (Frontiers in Earth Science, 2018)
The concentration and spatial distribution of major (Ca, Mg) and trace elements (Na, Sr, S, Li, Ba, Pb, and U) in different Corallium skeletons (C. rubrum, C. japonicum, C. elatius, C. konojoi) have been studied by electron microprobe (EMP) and laser ablation inductively coupled plasma mass spectrometry (LA-ICPMS). EMP data show positive Na-Mg and negative Na-S and Mg-S correlations in all skeletons. LA-ICPMS data display additional Sr-Mg, Li-Mg, and U-Mg positive correlations. Medullar zones in the skeletons, corresponding to fast growing zones, are systematically richer in Mg, Na, Sr, Li, and U and poorer in S than the surrounding slow growing zones. These spatial distributions are mostly interpreted in terms of growth kinetics combined with steric effects influencing the incorporation of impurities in biogenic calcites. This interpretation is in agreement with available experimental data on kinetic effects on the incorporation of elements in calcite. At a different scale, annual growth rings in annular slow growing zones show oscillations in Mg, Na, Sr, and S. These chemical oscillations probably result from growth rate variations: fast growth would produce rings enriched in Mg, Sr, and Na, while slow growth would produce rings enriched in S and organic matter. From previous studies in C. rubrum, the Mg-rich rings would develop during the spring to fall period while the S-rich rings would form immediately after (late fall and winter). Analytical traverses performed in annular zones of different Corallium skeletons indicate that Mg, Na, Sr, Li and U decrease from core to rim. This observation indicates that radial growth rate decreases as the colony gets older. Contrary to Mg, Na, Sr, Li, S and U, barium and lead concentrations are identical in medullar and annular zones and appear independent of growth kinetics. Thus, concentrations in Corallium skeletons could provide indications on Ba and Pb contents in the oceans. Barium and lead concentrations are higher in Mediterranean than in Pacific precious corals, they can be used to discriminate C. rubrum from C. japonicum, and contribute enforcing regulations on the trade of precious corals.